Предмет: Алгебра, автор: Serfey

Упростить выражение!!!

Приложения:

Ответы

Автор ответа: amin07am
0
Ответ ^/$#@$^&****^////&*******
Приложения:
Автор ответа: Munkush
0
frac{sqrt{frac{x+2}{x-2}}+sqrt{frac{x-2}{x+2}}}{sqrt{frac{x+2}{x-2}}-sqrt{frac{x-2}{x+2}}}=frac{left(sqrt{frac{x+2}{x-2}}+sqrt{frac{x-2}{x+2}}right)left(sqrt{frac{x+2}{x-2}}+sqrt{frac{x-2}{x+2}}right)}{left(sqrt{frac{x+2}{x-2}}-sqrt{frac{x-2}{x+2}}right)left(sqrt{frac{x+2}{x-2}}+sqrt{frac{x-2}{x+2}}right)}=frac{left(sqrt{frac{x+2}{x-2}}+sqrt{frac{x-2}{x+2}}right)^2}{frac{8x}{x^2-4}}= \

frac{left(sqrt{frac{x+2}{x-2}}+sqrt{frac{x-2}{x+2}}right)^2left(x^2-4right)}{8x}=frac{frac{2^2x^2}{left(x+2right)left(x-2right)}left(x^2-4right)}{8x}=frac{4x^2left(x+2right)left(x-2right)}{left(x+2right)left(x-2right)}=frac{4x^2left(x-2right)}{x-2}=

frac{4x^2}{8x}=frac{x^2}{2x}=frac{x}{2}

OTVET : frac{x}{2}
Приложения:
Похожие вопросы